A dynamic model of customer complaining behaviour from the perspective of service-dominant logic - Tronvoll, Bård (European journal of marketing, 2012)
Purpose - The purpose of this paper is to propose a conceptual model of customer complaining behaviour as a dynamic process in accordance with the service-dominant logic perspective of marketing.Design methodology approach - The study reviews the common behaviour models of customer complaints and relates this to the service-dominant logic perspective in order to develop and describe a dynamic conceptual model of customer complaining behaviour.Findings - The proposed model posits three categories of complaining behaviour due to a customer's unfavourable service experience: no complaining response, communication complaining responses, and action complaining responses.Research limitations implications - Empirical validation of the proposed conceptual model is needed.Practical implications - The proposed model can be used by managers to understand the various behaviour responses of customer complaints that the company experiences. In addition, the model assists in framing appropriate managerial responses, including service recovery and improved service design.Originality value - The study represents a thorough conceptual examination of the complaint process and proposes a dynamic model of customer complaining behaviour based on the service-dominant logic perspective.